ORAL AND SYSTEMIC COMPARATIVE ANALYSIS OF MALONDIALDEHYDE IN PATIENTS WITH DIABETES AND CHRONIC PERIODONTITIS - Daniel Cioloca; Amelia Surdu; Gina Botnariu; Filip Florina; Liliana Foia; Cătălina Holban Cioloca (Romanian Dental Association for Education, 2015)
The effects mediated by free radicals can scan severe destructions toward lethal effects on the cells. The oxidation of polyunsaturated fatty acids is one of the main effects, with the possibility of severe damage through oxidation of cellular enzymes. Objectives. The present clinical and biochemical study was designed to evaluate the role of serum and crevicular fluid (GCF) malondialdehyde (MDA) levels in patients with chronic periodontitis (CP) and diabetes mellitus (DM) as a marker of oxidative stress. Material and methods. The study group consisted of 40 subjects, aged 25-45 years. Subjects were divided into three groups according to clinical signs of periodontal alteration: group 1-control (n = 10) without systemic or periodontal alterations, group 2 (n = 15) with chronic periodontitis without diabetes, group 3 (n = 15 ) with diabetes and periodontal alter. For each patient serum and GCF MDA values have been evaluated. Results. Levels of MDA in both serum and GCF recorded the highest value for group 3, followed by average values in group 2, the lowest being registered in the control group. Conclusions. MDA may be a marker of oxidative stress in CP associated to DM